Learning Climate as a Predictor of Nurse Clinical Competence: A Cross-Sectional Regression Analysis - Muhammad Gilang Maulana; Wastu Adi Mulyono; Made Sumarwati (Fakultas Ilmu-ilmu Kesehatan Universitas Jenderal Soedirman, 2026)
Background: Clinical competence is essential for safe, high-quality nursing care. Workplace learning conditions (learning climate) may be a key organizational lever to strengthen competence among practicing nurses. Aim: To examine whether learning climate predicts nurses’ clinical competence in an Indonesian tertiary referral hospital. Methods: This associative cross-sectional study was conducted at Prof. Dr. Margono Soekarjo Hospital, Central Java, Indonesia (August–December 2025). A total of 125 registered nurses from IRNA 1 and the Emergency Department participated via total sampling. Learning climate was measured using the Clinical Learning Environment and Supervision (CLES) scale, while clinical competence was assessed using a 28-item questionnaire based on Indonesia’s Regulation No. 40/2017. Linear regression tested the predictive effect of learning climate on clinical competence (p < .05). Results: Participants’ mean age was 36.90 years (SD = 8.24) with mean work experience of 12.24 years (SD = 8.75). Mean learning climate and clinical competence scores were 113.52 (SD = 12.53) and 121.02 (SD = 10.05), respectively. Learning climate significantly predicted clinical competence (B = 0.615, p < .001), explaining substantial variance (R² = 596). Age and work experience were not significant predictors. Conclusion: A more supportive learning climate is associated with higher nurse clinical competence. Strengthening supervision, feedback, and learning opportunities may accelerate competence development and improve care quality.